Кондуит и Швамбрания: повесть / Л. А. Кассиль ; редактор А. А. Денискин - Кассиль Лев Абрамович (Репро, 2001)
Экземпляры: БС (20170725) / Инвентарный номер: РТШ49482 / Сис.шифр: Р2 / Авт.знак: К 28 / ГРНТИ: 17 / ББК: 84(2)